Mammary Gland Malignant Myoepithelioma in a Domestic Rabbit (Oryctolagus cuniculus) - Silva, Halana do Carmo; de Oliveira, Avisa Rodrigues; Horta, Rodrigo dos Santos; Moereira, Betânia Souza; Silveira, Tatiany Luiza; Cassali, Giovanni Dantas; Dantas, Mayra Cunha (Acta Scientiae Veterinariae, 2019)
Background: Malignant myoepithelioma is a rare neoplasm in humans and rats, poorly reported in dogs and not previously described in rabbits. This study aimed to report a case of malignant mammary myoepithelioma in a domestic rabbit (Oryctolagus cuniculus). Case: A domestic, hybrid, female, entire, nulliparous, seven-year-old rabbit was attended in the Veterinary Hospital Prof. Ricardo Alexandre Hippler at Universidade Vila Velha (UVV) with a history of apathy, lethargy and anorexia. In the clinical examination a 5 cm tumour was observed in the right abdominal mammary gland (M2), along with floating smaller lesions in M1 and M3. There were no palpable abnormalities in the axillary and inguinal lymph nodes. Complete blood count and serum biochemistry were within the normal range. Fine needle aspiration was performed for cytopathological evaluation of the tumour in M2 and it was suggestive of a malignant glandular neoplasm, with probable epithelial origin. Complete staging included chest and abdominal radiographs, but they were unremarkable. The patient was submitted to a right unilateral mastectomy, involving resection of the inguinal lymph node. The sample was sent to the Laboratory of Animal Pathology of UVV for routine histological evaluation. Histopathological evaluation in M2 was compatible with malignant myoepithelioma based on the literature, while nodules in M1 and M3 were classified as mammary cysts. The inguinal lymph node showed no significant abnormalities. An immunohistochemical panel was performed in the Comparative Pathology Laboratory of the Institute of Biological Sciences of the Universidade Federal de Minas Gerais (UFMG), using immunomarkers (pan-cytokeratin, p63 and vimentin) to characterize the tumour and confirm its diagnosis. Immunohistochemistry revealed expression of p63, and was negative for pan-cytokeratin and vimentin, which confirmed the myoepithelial origin, without involvement of the epithelial compartment. Clinical follow-up was recommended every 2-3 months, including abdominal ultrasonography, chest X-rays, complete blood count and serum biochemistry. Ultrasonography showed thinning of the uterine wall, dilation of 3.7 cm in diameter and presence of endometrial cysts of varied sizes, around 0.7 cm. Neutering was recommended but it was not elected by the pet´s responsible. These findings remained stable throughout the follow-up, which was greater than 405 days. Discussion: This is the first report of a malignant myoepithelioma in rabbit, with a detailed description of the clinical, surgical, pathological and immunophenotypic aspects of this neoplasm in this species. This is a tumour characterized by proliferation of epithelioid to spindle-like myoepithelial cells, as observed in this case, forming an extensive and well delimited solid area with marked central necrosis, compatible with what has already been described in the literature on bitches and women. As observed in this case, the neoplastic cells usually exhibit moderate cellular and nuclear pleomorphism, moderate anisocytosis and anisokaryosis, and several mitotic figures; different from what is observed in women, in which mitotic figures vary from small to moderate amount. Neoplasia and mammary cysts were removed by mastectomy, and the owner choose not to castrate the animal. On ultrasonography, after 12 months, the endometrium presented structures similar to cysts and was hyperplastic, which is commonly reported in association to mammary neoplasia. Nervertheless, the pet´s owner choose not to spay the rabbit and the lesions were stable on imaging follow-up